The limitations of the Nagoya Protocol in protecting genetic resources: evaluation of its impacts on the global community - Ansari, Abdul Haseeb (2012)
The Nagoya Protocol on Access to Genetic Resources and the Fair and Equitable Sharing of Benefits Arising from their Utilization to the Convention on Biological Diversity (CBD), an international protocol legally binding on user countries as well as provider countries was adopted by the CBD’s 10th Conference of the Parties on 30 October 2010 and opened for signature by parties to the CBD on 2 February 2011. The preliminary aim of the Protocol is to implement the CBD’s third objective on fair and equitable sharing of benefits. For permitted access, users of genetic resources are obliged to share benefits arising from the utilization of such resources with the providers; benefits, which help providers to develop their own sustainable uses and to preserve biodiversity. However, the provisions of the Protocol when viewed in totality have various limitations in effectively conserving and enhancing the global genetic resources. This paper analyzes these limitations and suggests measures which can be jointly undertaken by the global community to prevent the rapid loss of biodiversity.